2012
DOI: 10.1016/j.orgel.2012.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Optically-enhanced performance of polymer solar cells with low concentration of gold nanorods in the anodic buffer layer

Abstract: Abstract:In this work, the effect of gold nanorods on the performance of poly(3-hexylthiophene-2,5-diyl):[6,6]-phenyl-C 61 -butyric-acid-methyl-ester bulk heterojunction solar cells was investigated. Gold nanorods were introduced into the anodic buffer layer by simply blending them with the solution of poly(3,4-ethyl-enedioxythiophene):poly(styrenesulfonate). Even with a fairly low density of the nanorods, the resulting devices showed a remarkable 21.3% enhancement in the power conversion efficiency and a 13% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…(Φ sat) at Ts = 556 K is found to be 5.10 eV in agreement with those values found by the others [24]- [29]. This value lies close to that obtained by Huber [22] (5.22 eV) using Contact Potential Difference, Jones et al, [20], and Jones et al [21] in their studies of gold adsorption on tungsten obtained values of 5.23 eV and 5.20 eV respectively, but our results do not agree with the values obtained by Frederisken et al [34] and Salisbury et al [35].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…(Φ sat) at Ts = 556 K is found to be 5.10 eV in agreement with those values found by the others [24]- [29]. This value lies close to that obtained by Huber [22] (5.22 eV) using Contact Potential Difference, Jones et al, [20], and Jones et al [21] in their studies of gold adsorption on tungsten obtained values of 5.23 eV and 5.20 eV respectively, but our results do not agree with the values obtained by Frederisken et al [34] and Salisbury et al [35].…”
Section: Discussionsupporting
confidence: 90%
“…Our results of (Φ sat) of gold adsorption on iridium total emitter surface are shown to be in agreement with the results of the other workers [20] [21] [22] [23]. A value of 5.1 eV was observed by [24]- [29], while Farrer et al [30] and Trouwborst et al [31] observed that the value of the work function of gold was less than 5.1 eV which is less than our value. Abid et al [32] observed a value of 5.2 eV which is in the range of our values.…”
Section: Variation Of Electron Work Function (φ) With Gold Coverage (θ)supporting
confidence: 92%
“…Besides, the longitudinal absorption peak of the rods is close to the IR absorption edge of the photoactive film. Hence, the intensified EM field around Au NRs would increase the absorption of the photoactive film near the plasmon peaks of the rods, in which an enhancement in the film absorption near the IR region is expected [14,18].…”
Section: Characterizationsmentioning
confidence: 99%
“…Such resonance allows MNPs to absorb light in the visible region of the spectra, leading to intensification, by a factor of 100, in the electromagnetic (EM) field surrounding them [5]. Metallic nanoparticles are widely used in thin-film solar cells to enhance their absorption of light by utilizing the far-field and near-field effect associated with their localized surface plasmon resonance (LSPR) [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation